2015
DOI: 10.1292/jvms.14-0647
|View full text |Cite
|
Sign up to set email alerts
|

Dark adaptation time in canine electroretinography using a contact lens electrode with a built-in light source

Abstract: The purpose of this study was to evaluate the dark adaptation time in canine electroretinography (ERG) using a contact lens electrode with a built-in LED. Twelve eyes of six normal laboratory beagle dogs were used and exposed to steady room light at 500 lux for 30 min for light adaption. ERG was recorded at different time points during dark adaptation in sedated and light-adapted beagles. The stimulus intensity was 0.0096 cd/m2/sec. The b-wave amplitude increased significantly until 25 min of dark adaptation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
3
3
0
Order By: Relevance
“…In agreement with previous studies in rodents [26,29,33], canines [25] and humans [20], we demonstrated that the implicit times of the flash ERGs decreased during light adaptation as well as during dark adaption. As proposed above for their corresponding amplitudes, the sudden increase after background light onset and subsequent decrease in implicit times over both light/dark adaptation periods is probably also a general recovery after an instantaneous change in implicit time following the alteration in adaptation level.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with previous studies in rodents [26,29,33], canines [25] and humans [20], we demonstrated that the implicit times of the flash ERGs decreased during light adaptation as well as during dark adaption. As proposed above for their corresponding amplitudes, the sudden increase after background light onset and subsequent decrease in implicit times over both light/dark adaptation periods is probably also a general recovery after an instantaneous change in implicit time following the alteration in adaptation level.…”
Section: Discussionsupporting
confidence: 93%
“…Although there are studies that describe the changes in cone or rod ERGs after bleaching of the retina using paired flash stimuli [30,31,32], there are not many data about ERG responsivity changes during dark adaptation that are recorded with single flash ERGs or flicker ERGs. Li et al [33] found an increase in amplitude and a decrease in latency in rodents during dark adaptation, which is similar to the results in the study of Maehara et al [25] in canines.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…The determination of normal ERG values is of great importance for clinical practice, considering that there are numerous intrinsic and extrinsic factors influencing the ERG recordings including the age and breeds of the animal (Itoh et al, 2010), the environment and body temperature (Mizota and Adachi-Usami, 2002), pupil diameter, intraocular pressure and eye movement (Marmor et al, 2009;Grozdanic et al, 2010;Nair et al, 2011), electrode type and position (Mentzer et al, 2005), stage of retinal dark adaptation (Maehara et al, 2015), anesthesia technique (Norman et al, 2008;Lin et al, 2009). All of that contribute to interfere with the values obtained from ERG recording; therefore, the investigations aiming to establish a normal range still continue.…”
mentioning
confidence: 99%